2017
DOI: 10.1371/journal.pone.0187111
|View full text |Cite
|
Sign up to set email alerts
|

The pacing strategy and technique of male cross-country skiers with different levels of performance during a 15-km classical race

Abstract: In this study the pacing strategy, cycle characteristics and choice of technique of elite male cross-country (XC) skiers during a three-lap, 15-km classical race with interval start were measured. During the Norwegian Championships in 2016, fast (n = 18, age: 26±4 yr; height: 182±4 cm; body mass: 78±3 kg (means±SD)) and slow skiers (n = 18, age: 22±2 yr; height: 183±5 cm; body mass: 78±6 kg) were video recorded on flat (0°), intermediate (3.5°) and uphill sections (7.1°) of the first and final laps. All skiers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 25 publications
(56 reference statements)
6
50
1
Order By: Relevance
“…The already mentioned importance of a well-developed upper body capacity during XCS is also fostered when using the strategy to exclusively DP a long-distance race. During the past three decades, in XCS, the DP technique has become more and more extensively utilized, and today, its successful usage determines the outcome of classic style XCS races (Holmberg et al, 2005;Stöggl and Holmberg, 2011;Sandbakk and Holmberg, 2014;Welde et al, 2017;Jonsson et al, 2019;Stöggl et al, 2019). Stöggl et al (2019) recently demonstrated that elite male skiers were faster with exclusive DP compared with grip-waxed skis on an FIShomologated race track over 5 km, but with no performance benefits for junior skiers and clearly lower in female juniors and seniors.…”
Section: Exclusive Dpmentioning
confidence: 99%
“…The already mentioned importance of a well-developed upper body capacity during XCS is also fostered when using the strategy to exclusively DP a long-distance race. During the past three decades, in XCS, the DP technique has become more and more extensively utilized, and today, its successful usage determines the outcome of classic style XCS races (Holmberg et al, 2005;Stöggl and Holmberg, 2011;Sandbakk and Holmberg, 2014;Welde et al, 2017;Jonsson et al, 2019;Stöggl et al, 2019). Stöggl et al (2019) recently demonstrated that elite male skiers were faster with exclusive DP compared with grip-waxed skis on an FIShomologated race track over 5 km, but with no performance benefits for junior skiers and clearly lower in female juniors and seniors.…”
Section: Exclusive Dpmentioning
confidence: 99%
“…For the Likert scale and image quality data, the distances between any two adjacent points along the rating scale were assumed to be equal, and all these data were treated as interval-like. The effect size was interpreted as low, medium, or high when the partial η 2 was 0.01, 0.06, or 0.14, respectively [76,77]. A stepwise multiple linear regression analysis was performed to examine the degree to which user satisfaction variability (satisfaction associated with watching TV) was accounted for by the other six TV watching experience elements.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Another factor that was not controlled for in the present study was the technique (double poling, diagonal stride, and kick double poling) of XC skiers, which might influence pacing since it has been shown to be related with performance level. 22 , 23 In addition, due to the large sample size, many effects reached statistical significance at p < 0.001; this is the reason that we provided effect size value next to p value so one can evaluate the magnitude of the effects correctly. However, a strength of the study is the inclusion of all occurrences of the Vasaloppet race (2004‐2017) for which all split times were available, resulting in one of the largest samples of XC skiers ever studied.…”
Section: Discussionmentioning
confidence: 99%